Bus crew scheduling system for Unit Kenderaan UiTM / Siti Fatimah Abidin - Abidin, Siti Fatimah (2007)
This research is conducted to assist Unit Kenderaan executive officer to manage the bus crew scheduling activities through an information system in order to provide effectiveness and efficiency of that activity. The purposes of this research are to identify the requirements and data needed in developing Bus Crew Scheduling System (BCSS), to analyze the requirements captured and data gathered to design the BCSS and to develop Bus Crew Scheduling System for Unit Kenderaan UiTM. Interviews, reading journals and study the existing system are among the methods used in conducting this research. This system is developed using Apache Web Server, MySQL Database, phpMyAdmin Database Administrator, PHP programming language and ActiveXperts SMS Messaging Server. This system automates the process of producing bus crew schedule. The officer can keep track the recent status of bus crew to make decision during emergency adjustment of the crew schedule. SMS notification is used as one way to notify the crew for any daily duty replacement. This system also provides crew monthly duty graph to support the officer during the duty distribution. Therefore the development of this system is hoped to be beneficial in term of integrating, transferring, and getting updated data and information faster and easier.